A genetically selected cyclic peptide inhibitor of BCL6 homodimerization. Issue 11 (15th July 2018) - Osher, Eliot L.; Castillo, Francisco; Elumalai, Nagarajan; Waring, Michael J.; Pairaudeau, Garry; Tavassoli, Ali
Graphical abstract: Abstract: We report an inhibitor of the homodimeric protein-protein interaction of the BCL6 oncoprotein, identified from a genetically encoded SICLOPPS library of 3.2 million cyclic hexapeptides in combination with a bacterial reverse two-hybrid system. This cyclic peptide is shown to bind the BTB domain of BCL6, disrupts its homodimerization, and subsequent binding of the SMRT2 corepressor peptide.